2012
DOI: 10.1097/iae.0b013e318242b9ab
|View full text |Cite
|
Sign up to set email alerts
|

Half-Fluence Photodynamic Therapy in Acute Central Serous Chorioretinopathy

Abstract: Indocyanine green angiography-guided half-fluence photodynamic therapy with verteporfin is effective in treating acute symptomatic central serous chorioretinopathy, resulting in visual improvement and complete resolution of exudative macular detachment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 26 publications
1
19
1
Order By: Relevance
“…[1][2][3][15][16][17][18][19][20][21] In a retrospective study, Mudvari et al 29 found that none of the 340 consecutive CSCR patients developed CNV during an approximate 4-year follow-up period (mean of 49 months). However, Spaide et al 30 reported that older patients with CSCR had a lower VA, and were more likely to have diffuse retinal pigment epitheliopathy and secondary CNV than their younger counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3][15][16][17][18][19][20][21] In a retrospective study, Mudvari et al 29 found that none of the 340 consecutive CSCR patients developed CNV during an approximate 4-year follow-up period (mean of 49 months). However, Spaide et al 30 reported that older patients with CSCR had a lower VA, and were more likely to have diffuse retinal pigment epitheliopathy and secondary CNV than their younger counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, experience due to previous studies conducted at our tertiary center on acute and chronic CSCR enabled us to follow a PDT regimen, using half-dose fluence rate (25 J/cm 2 ), while not changing the dose of verteporfin (6 mg/m 2 ). [16][17][18] Selecting an appropriate fluence rate helps avoiding collateral damage as atrophy of the RPE, choroidal ischemia, and development of secondary CNV due to less choriocapillaris damage. [18][19][20] Said avoidance of negative treatment effect of RPE's metabolic activity was shown in a study of Hagen et al, 36 where the focus was set on RPE alterations in eyes with acute CSCR treated with half-fluence PDT observed via shortwavelength fundus autofluorescence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To avoid the potential complications of conventional PDT, the patients had undergone a modified fluence PDT-reduced time of laser emission (50 s) and total light energy (30 J/cm 2 ), using the standard dose of verteporfin (6 mg/m 2 ) and laser intensity (600 mW/cm 2 ). 4,5,14,[17][18][19] The PDT spot size was determined by measuring the greatest linear dimension of the area of choroidal vascular hyperpermeability, corresponding to the origin of subfoveal fluid on ICGA. Patients receiving PDT were followed up and BCVA and SFCT using EDI-OCT at 7 day and 1 month after treatment were evaluated.…”
Section: Methodsmentioning
confidence: 99%